Multiple peer-assessment modes to augment online student question-generation processes - Yu, Fu-Yun (Computers and education, 2011)
In view of the current theoretical and empirical support for a student-generated questions approach to learning along with the advantageous features of network technology, several online student question-generation learning systems with a peer-assessment component have been developed. Despite this, all existing systems are limited in terms of the types of communication modes permissible for peer-assessment. Online discourse experience and the quantity and quality of interaction may vary as a result of the specific interaction mode students are exposed to. Because of this and the fact that versatile learning spaces are both possible and potentially desirable during the various stages of learning and teaching, multiple peer-assessment modes were created, and the overall attitudes of learners toward peer-assessment as well as their preferences toward respective peer-assessment modes were examined. The collected data confirmed the perceived usefulness of peer-assessment for developing higher-order thinking and cognitive elaboration. Support was demonstrated for student question-generation activities, for which learners typically have limited prior experience. Additionally, in light of the apparent overwhelming preference for and superiority of the more interactive two-way and multi-way modes over the one-way mode and the perceived learning potential of these modes, it is suggested that designers of similar systems should consider their inclusion. Finally, even though multi-way learning was found to be both the preferred and most supportive mode for learning, students also revealed distinct reasons for their preferences for respective interaction modes. In general, these reasons supported the premise that multiple peer-assessment modes are needed in order to accommodate individual preferences and needs. Suggestions and implications for instructional implementation, system development, and future studies are offered.